2010
DOI: 10.1089/end.2009.0438
|View full text |Cite
|
Sign up to set email alerts
|

CyberKnife Stereotactic Radiotherapy as Monotherapy for Low- to Intermediate-Stage Prostate Cancer: Early Experience, Feasibility, and Tolerance

Abstract: This regimen of stereotactic CK monotherapy for low- to intermediate-risk prostate cancer with excellent dose coverage of the prostate was well tolerated. Data collection is ongoing for further assessment of toxicity and PSA response.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
48
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 50 publications
(50 citation statements)
references
References 26 publications
2
48
0
Order By: Relevance
“…Stereotactic body radiotherapy (SBRT) has recently emerged as an alternative technique to deliver hypofractionated radiotherapy to the prostate, comparable in many respects to HDR brachytherapy, but with a noninvasive approach [8][9][10][11][12][13][14]. The concept is not entirely novel.…”
Section: Introductionmentioning
confidence: 99%
“…Stereotactic body radiotherapy (SBRT) has recently emerged as an alternative technique to deliver hypofractionated radiotherapy to the prostate, comparable in many respects to HDR brachytherapy, but with a noninvasive approach [8][9][10][11][12][13][14]. The concept is not entirely novel.…”
Section: Introductionmentioning
confidence: 99%
“…Consequently, researchers have used brachytherapy as a boost within the prostate following EBRT or IMRT delivery of [45][46][47][48][49][50] Gy to the prostate and surrounding tissues. As noted earlier, HDR brachytherapy as a boost to EBRT or IMRT can achieve 5-8 year freedom from biochemical failure rates of 85-90% and 68-73% for intermediate-and high-risk disease, respectively [23,57].…”
Section: Sbrt As a Boost For Higher Risk Diseasementioning
confidence: 99%
“…At a median follow-up of 18 months 87% percent (198/228) of patients maintained erectile (Friedland et al 2009). The results of other published but small single-institution trials are summarized in Table 11 (Katz et al 2010;Wiegner and King 2010;Aluwini et al 2010;Friedland et al 2009;King et al 2009;Morgia and De Renzis 2009;Fuller et al 2008;Madsen et al 2007). Several randomised trials have indicated that by increasing the dose to the prostate better biochemical control is obtained.…”
Section: Sbrt For Prostate Cancermentioning
confidence: 99%
“…As is the case for conventionally fractionated external beam radiotherapy for prostate cancer there is no consensus on rectal preparation and bladder filling in stereotactic radiotherapy. Some authors advocate the use of low fiber diets and pre-treatment laxatives (Aluwini et al 2010) or anti flatulent medication after each meal (Madsen et al 2003). However, so far none of these approaches was proven to be superior.…”
Section: Sbrt For Prostate Cancermentioning
confidence: 99%